High Average Power Near-Infrared Few-Cycle Lasers - Rothhardt, Jan; Haedrich, S.; Delagnes, J. C.; Cormier, E.; Limpert, Jens (Laser & Photonics Reviews, 2017)
Ultra-short laser pulses with only a few optical cycles duration have gained increasing importance during the recent decade and are currently employed in many laboratories worldwide. In addition, modern laser technology nowadays can provide few-cycle pulses at very high average power which advances established studies and opens exciting novel research opportunities. In this paper, the two complementary approaches for providing few-cycle pulses at high average power, namely optical parametric amplification and nonlinear pulse compression, are reviewed and compared. In addition, their limitations and future scaling potential are discussed. Furthermore, selected applications particularly taking advantage of the high average power and high repetition rate are presented.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Few-cycle pulses; high power lasers; nonlinear compression; Optical parametric amplification